2020
DOI: 10.1155/2020/8076259
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Factors Associated with Healthcare Utilization for Childhood Diarrhea and Fever in Ethiopia: Further Analysis of the Demographic and Health Surveys from 2000 to 2016

Abstract: Background. Healthcare use for childhood illness reduces the risk of under-five deaths from common preventable diseases. However, rates of healthcare seeking for childhood diarrhea and fever remain low in most low- and middle-income countries including Ethiopia. This study aimed to assess the trends and factors for healthcare diarrhea and fever in Ethiopia from 2000 to 2016. Methods. Analysis of healthcare use for diarrhea and fever trends was done using data from four Ethiopian Demographic Health Surveys. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
15
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 19 publications
9
15
2
Order By: Relevance
“…It was found that children whose birth order 4 th and above were more likely to be affected by diarrhea than 1st order children. It coincides with the previous studies in which birth order of a child increases and the probability of developing childhood diarrhea increases [ 8 , 15 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…It was found that children whose birth order 4 th and above were more likely to be affected by diarrhea than 1st order children. It coincides with the previous studies in which birth order of a child increases and the probability of developing childhood diarrhea increases [ 8 , 15 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…Health insurance enables women to afford medical care, freely choose the type of care and choose between medical institutions according to their needs and expectations of care, without worrying about the cost [17]. We further observed that access to mass media showed decreased odds of healthcare accessibility barriers, which confirms previous studies in Ethiopia [47], India [48], Bangladesh [49], and rural Malawi [50]. The reason for this could be that listening to the radio and watching television increases ones' health literacy, which has been identified as key to healthcare utilization [51].…”
Section: Discussionsupporting
confidence: 88%
“…Exposure to mass media also showed decreased odds of healthcare accessibility barriers, which corroborates earlier studies in Ethiopia [ 40 ], India [ 41 ], Bangladesh [ 42 ], and rural Malawi [ 43 ]. The reason for this could be that listening to radio, reading newspaper, and watching television increase ones’ health literacy, which has been identified as a key enabler to healthcare utilization [ 44 ].…”
Section: Discussionsupporting
confidence: 88%